2013
DOI: 10.1002/anie.201304099
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth(V)‐Mediated Thioglycoside Activation

Abstract: Chemical glycosylation [1,2] is a crucial step in any oligosaccharide [3] synthesis. [4,5] Among the different classes of commonly used glycosyl donors, [2] thioglycosides [6, 7] offer distinct advantages. Thioglycoside donors are relatively simple to prepare, are stable under various reactions for protectinggroup manipulations, and offer orthogonality in their activation in the presence of other glycosyl donors. [8] As a result, a wide variety of promoters have been developed for activation of these donors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 56 publications
1
44
0
Order By: Relevance
“…[180b] The use of Bi V Lewis acids is less advanced. [186] Bismuth pentafluoride is highly oxidizing and ap owerful fluorination agent. [187] Its Lewis acidity is certainly substantial but expected to be lower than that of SbF 5 .…”
Section: Group 15mentioning
confidence: 99%
“…[180b] The use of Bi V Lewis acids is less advanced. [186] Bismuth pentafluoride is highly oxidizing and ap owerful fluorination agent. [187] Its Lewis acidity is certainly substantial but expected to be lower than that of SbF 5 .…”
Section: Group 15mentioning
confidence: 99%
“…Introducing a novel promoter‐free glycosylation technique, Pohl and co‐workers efficiently used sub‐stoichiometric amounts of triphenyl bismuth ditriflate [Ph 3 Bi(OTf) 2 ] to activate various thiopropyl glycosides . The highly robust nature and solubility of bismuth(V) salts made it a highly advantageous glycosylation catalyst, employing just catalytic amounts of the promoter.…”
Section: Glycosylationsmentioning
confidence: 99%
“…A survey of bismuth carboxylates, [3][4][5][6][7][8][9][10] sulfonates [11][12][13][14][15][16][17][18][19] and sulfonatocarboxylates 20,21,22 demonstrated that IBUs in the crystal structures range from mononuclear complexes to Bi-O clusters with up to 38 bismuth ions to infinite Bi-O chains and even Bi-O layers. While the Bi-O clusters and dinuclear IBUs are mostly formed through reactions at room temperature or hydrolysis at moderate temperatures, respectively, the Bi-O chains were mostly obtained employing hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%